(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The current research aimed to explore the pragmatic language disorders according to some variables (age, sex, executive functions), the total sample consisted of 12 children ranged between (6-11 years) boys and girls, the researcher has used the descriptive approach. The results showed that there were differences between the members of the younger age group and members of the older age group of the sample of autism spectrum children on the pragmatic language disorders scale. According to the gender variable, there were no significant differences between male and female of the sample of autism spectrum children on the pragmatic language disorders. It was also found that there were statistically significant relationship between pragmatic language disorders and executive functions. In other word, children who have poor executive functions on executive function rating scale have more difficulties in pragmatic language.